La ocupación del espacio musical en Escrito sobre escrito sobre escrito de Marcelo Delgado (Cuadernos de Análisis y Debate sobre Músicas Latinoamericanas Contemporáneas, 2021)
This article studies intertextual spaces that appear in a rewriting work done by Marcelo Delgado based on Eusebius by Gerardo Gandini. The analytical research will take the technique Cantus firmus as a historical reference. Thus, it will provide a framework to analyze the configuration of a musical and intertextual space widened by the recognition of interval-class content and pitch-class sets that refer to musical piece No. 14 of the piano cycle DavidsbündlertÁ¤nze (1837) by Robert Schumann. As a final stage, the palimpsest metaphor is followed to interpret the relations derived from this analysis.
Keywords: Cantus firmus; appropriation; Gerardo Gandini; rewriting; palimpsest; Robert Schumann